PENGARUH LINGKUNGAN KERJA, STRES DAN DISIPLIN KERJA TERHADAP PERSEPSI KINERJA KARYAWAN TEKNOLOGI INFORMASI (TI) DI PT.E - Audrianne Caitlyn Beng; William Widjaja (Publika Citra Media, 2026)
This research aims to examine the effect of work environment, stress and work discipline on employee performance perceptions at PT.E that operates in the information technology (IT) sector. This research uses a quantitative approach, with primary data being collected through questionnaires distributed to 31 employees of PT.E. The results indicate that the work environment has a negative and insignificant effect on employee performance perceptions, as evidenced by a t-value of 1.511, which is lower than the t-table value of 1.703, and a significance value greater than 0.05. The second variable, work stress, also has a negative and insignificant effect on employee performance perceptions, with a t-value of -0.331, which is lower than the t-table value of 1.703, and a significance value of 0.743, exceeding 0.05. The third variable, work discipline, has a positive and significant effect on employee performance perceptions, with a t-value of 2.680, which is higher than the t-table value of 1.703, and a significance value of 0.012, which is lower than 0.05. This study is expected to serve as a consideration for companies in improving employee performance perceptions by managing the work environment, stress levels, and work discipline better.